Exploration of Leaf Moss Species (Bryophyta) in the Gedong Songo Temple Area, Bandungan, Central Java - Salsabila, Mutiara Syafila; Khotimperwati, Lilih; Kinasih, Anggiresti (Biotropika: Journal of Tropical Biology, 2026)
Gedong Songo Temple Area is located on the slopes of Mount Ungaran, Central Java, and exhibits a high diversity of microhabitats, ranging from open areas around the temple structures, humid natural forests, to geothermal zones influenced by sulfur. These conditions potentially support a high diversity of mosses (Bryophyta); however, information on species composition in this area remains limited. This study aimed to explore the diversity and relative frequency of mosses across contrasting microhabitats. The research was conducted in four sites: the area near Temple I, the area near sulfur sources, the forest area near an inactive crater, and natural forest areas, using a plot method. Epiphytic mosses were sampled on thirteen host trees using three 20 × 30 cm quadrats placed on different sides of each trunk. Meanwhile, terrestrial moss sampling was conducted using five plots measuring 1 m × 1 m on soil or rock surfaces at each station. The exploration recorded 32 moss species belonging to 20 genera, 13 families, one class, Bryopsida. Relative frequency (FR) across the entire area indicated that Ectropothecium monumentorum, Entodon sp., and Scopelophila sp. were among the most widely distributed taxa (FR= 8.77%). These results indicate that differences in microhabitat conditions, particularly humidity, light intensity, substrate type, and sulfur exposure, influence the occurrence and distribution of moss species in the Gedong Songo Temple Area.